Effects of ingesting protein with various forms of carbohydrate following resistance-exercise on substrate availability and markers of anabolism, catabolism, and immunity - Greenwood Michael; Rasmussen Christopher; Lundberg Jennifer; Earnest Conrad P; Kreider Richard B; Cowan Patricia; Almada Anthony L (Taylor & Francis Group, 2007)
Abstract Background Ingestion of carbohydrate (CHO) and protein (PRO) following intense exercise has been reported to increase insulin levels, optimize glycogen resynthesis, enhance PRO synthesis, and lessen the immuno-suppressive effects of intense exercise. Since different forms of CHO have varying glycemic effects, the purpose of this study was to determine whether the type of CHO ingested with PRO following resistance-exercise affects blood glucose availability and insulin levels, markers of anabolism and catabolism, and/or general immune markers. Methods 40 resistance-trained subjects performed a standardized resistance training workout and then ingested in a double blind and randomized manner 40 g of whey PRO with 120 g of sucrose (S), honey powder (H), or maltodextrin (M). A non-supplemented control group (C) was also evaluated. Blood samples were collected prior to and following exercise as well as 30, 60, 90, and 120 min after ingestion of the supplements. Data were analyzed by repeated measures ANOVA or ANCOVA using baseline values as a covariate if necessary. Results Glucose concentration 30 min following ingestion showed the H group (7.12 ± 0.2 mmol/L) to be greater than S (5.53 ± 0.6 mmol/L; p < 0.03); M (6.02 ± 0.8 mmol/L; p < 0.05), and C (5.44 ± 0.18 mmol/L; p < 0.0002) groups. No significant differences were observed among groups in glucose area under the curve (AUC) values, although the H group showed a trend versus control (p = 0.06). Insulin response for each treatment was significant by time (p < 0.0001), treatment (p < 0.0001) and AUC (p < 0.0001). 30-min peak post-feeding insulin for S (136.2 ± 15.6 uIU/mL), H (150.1 ± 25.39 uIU/mL), and M (154.8 ± 18.9 uIU/mL) were greater than C (8.7 ± 2.9 uIU/mL) as was AUC with no significant differences observed among types of CHO. No significant group × time effects were observed among groups in testosterone, cortisol, the ratio of testosterone to cortisol, muscle and liver enzymes, or general markers of immunity. Conclusion CHO and PRO ingestion following exercise significantly influences glucose and insulin concentrations. Although some trends were observed suggesting that H maintained blood glucose levels to a better degree, no significant differences were observed among types of CHO ingested on insulin levels. These findings suggest that each of these forms of CHO can serve as effective sources of CHO to ingest with PRO in and attempt to promote post-exercise anabolic responses.